The Disclosure of a Murder Case Using Fingerprint Identification Method: An Alternative - Randy Pradityo; Herlambang Herlambang; Helda Rahmasari; Galih Purwo (Unnes Law Journal, 2022)
This study aims to identify the function and role of fingerprints as a tool in the disclosures of a crime and the identification of the victim and suspect. It was conducted in the jurisdiction of the Bengkulu Regional Police. Data were collected data by direct interviews and documentation. Data were analyzed using qualitative techniques and then presented descriptively by providing descriptions and explanations in accordance with the problems of the study. The results showed that the function and role of fingerprint identification to scientifically disclose the victim and suspect of a crime was very important. Fingerprint identification functions as a tool or evidence for investigators to first determine and narrow the investigation.